Architecture from an Alternative Power - Rui del Pino Fernandes; João Cunha Borges; Teresa Marat-Mendes (Joelho)
In a revolution, governors can no longer govern, and the governed refuse to be so. In this sense, the experience of the Portuguese Local Support Service (Serviço de Apoio Ambulatório Local—SAAL) epitomizes the national revolution of 1974–5, allowing poor city workers to reclaim the right to housing and the city. This essay discusses the Catujal Workers Estate, built in this context, in Loures (Lisbon Region) with a plan by the brigade led by architect Francisco Pires Keil do Amaral. Most information is derived from the reports and drawings of the original SAAL intervention, with the aim of presenting an observation of this case and trying to highlight the process of cooperation that linked those designing the habitat with those who were to live in it.